Peningkatan Keterampilan Numerasi Peserta Didik Kelas IV Melalui Penerapan Pendekatan Game Based Learning - Arta Diva Firya Kirana, Riyadi (Didaktika Dwija Indria, 2025)
This classroom action research investigated the effectiveness of Game-Based Learning (GBL) in improving fourth-grade students' numeracy skills at SDN Sumber 6 Surakarta. The study was conducted over three cycles, implementing a structured approach involving problem orientation, strategy analysis, evaluation, reward, and reflection phases. Data collection utilized observation sheets, numeracy skills assessments, and student interviews to comprehensively evaluate learning outcomes.The research demonstrated remarkable improvements in student numeracy performance. Classical completeness rates increased dramatically from 0% during the pre-action baseline phase to 85.71% by the completion of the third cycle. This substantial enhancement indicates the significant impact of GBL methodology on mathematical learning outcomes.The findings confirm that Game-Based Learning effectively enhances student engagement and motivation while strengthening conceptual understanding in mathematics education. The systematic implementation of gaming elements in numeracy instruction proved to be a valuable pedagogical strategy for elementary mathematics teaching, suggesting its potential for broader educational applications.